Association of Erythrocyte Sedimentation Rate with Treatment Outcome in Patients Suffering from Pulmonary Tuberculosis: A Cross-Sectional Study in Islamabad - Afzal, Muhammad; Hassan, Zubia; Afzal, Saad; Azhar, Rimsha; Qureshi, Huzaifa; Hassan, Samra (Life and Science, 2025)
Objective: To assess the association of erythrocyte sedimentation rate with treatment outcome in patientssuffering from pulmonary tuberculosis.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Medicine, Margalla GeneralHospital, Islamabad, Pakistan from July 2022 to January 2023.Methods: Patients who were diagnosed with pulmonary tuberculosis by a consultant pulmonologist based onclinical and radiological criteria were included in the study. They underwent all baseline investigations,including erythrocyte sedimentation rate, at the time of diagnosis. Patients were started on the usualtreatment of pulmonary tuberculosis and followed up for three months. At the end of three months, clinicaloutcome was determined along with repetition of erythrocyte sedimentation rate, and the associationbetween both parameters was assessed.Results: A total of eighty-seven patients with pulmonary tuberculosis were included in the final analysis afterapplication of inclusion/exclusion criteria. AT the end of three months, 70 (80.4%) patients had significantclinical improvement, while 17 (19.6%) did not show significant clinical improvement. 77 (88.5%) patients hadan Erythrocyte sedimentation rate less than 50mm/h while 10 (11.5%) had more than 50mm/h. Chi-squareanalysis showed that reduced levels of Erythrocyte sedimentation rate had a statistically significant relationshipwith the presence of clinical improvement at the end of three months of treatment (P-value<0.001).Conclusion: Reduction in Erythrocyte sedimentation rate was found to be associated with clinical improvementat the end of three months of treatment in patients suffering from pulmonary tuberculosis. As a cost-effectivebiochemical marker associated with clinical improvement, it can be effectively incorporated into patientmanagement plans. How to cite this: Afzal M, Hassan Z, Afzal S, Azhar R, Quershi H, Hassan S. Association of Erythrocyte Sedimentation Rate with Treatment Outcome in Patients Suffering from Pulmonary Tuberculosis: A Cross-Sectional Study in Islamabad. Life and Science. 2025; 6(3): 399-404. doi: http://doi.org/10.37185/LnS.1.1.605